Space, Time and the Constitution of Subjectivity: Comparing Elias and Foucault. - Dolan, Paddy (Foucault Studies, 2010)
The work of Foucault and Elias has been compared before in the social sciences and humanities, but here I argue that the main distinction between their approaches to the construction of subjectivity is the relative importance of space and time in their accounts. This is not just a matter of the "history of ideas," as providing for the temporal dimension more fully in theories of subjectivity and the habitus allows for a greater understanding of how ways of being, acting and feeling in different spaces are related but largely unintended. Here I argue that discursive practices, governmental operations and technologies of the self (explanatory claims of both Foucault and the Foucauldian tradition) take shape as processes within the continuities of the figurational flow connecting people across space and time. Continuity should not be understood as stability or sameness over time, but as the contingent relations between successive social formations. As Elias argues, there is a structure or order to long-term social change, albeit unplanned, and this ultimately provides the broader social explanation for the historicity of the subject. Though discursive practices happen in particular spaces, we must recognise these spaces, and the practices therein, as socially constructed over time in response to largely unplanned moral and cultural developments.